(untitled) (Nigerian Journal of Technology, 2013)
Soil erosion data generated while estimating soil loss in Samaru, Zaria using the EUROSEM model were used as input parameters for the prediction of soil loss in the same catchment area using the WEPP erosion model. A comparative analysis of both models for soil loss prediction showed that WEPP performed better for bare and cultivated soils for which there was a continuous trend of increase in soil loss with advancement of years which was also in agreement with the observed values.